LiAlH4‐Promoted Tandem Reduction/Oxidation of Fluorenyl Derivatives under Air. Issue 29 (27th August 2014) - Matviiuk, Tetiana; Menendez, Christophe; Carayon, Chantal; Saffon, Nathalie; Voitenko, Zoia; Lherbet, Christian; Baltas, Michel
Abstract: The tandem reduction/oxidation of fluorenyl compounds was performed with LiAlH4 under air to afford the corresponding 9‐hydroxyfluorenyl derivatives in good yields. This methodology with LiAlH4 is unprecedented and most likely proceeds by an organoaluminium intermediate, and in the proposed mechanism. Abstract : The tandem reduction/oxidation of fluorenyl compounds with LiAlH4 under air affords the corresponding 9‐hydroxyfluorenyl derivatives in good yields.